Evidence in Civil Law - Germany - Wolf, Christian (Law & Society, 2015)
The fundamental principles in civil procedure do not only serve as guiding principles for civil procedure in general, but are especially relevant in the taking of evidence process. The German Code of Civil Procedure lays down various rules in its part on the taking of evidence, which aim to specify the scope of the fundamental procedural principles as well as their limitations. This reports purposes to depict the taking of evidence process under German law by illustrating its interaction with said principles.